Abnormal amplitude of low-frequency fluctuation values as a neuroimaging biomarker for major depressive disorder with suicidal attempts in adolescents: A resting-state fMRI and support vector machine analysis - Zhou, Yang; Song, Yu; Chen, Cheng; Yan, Shu; Chen, Mo; Liu, Tao (Frontiers in Psychology, 2023)
Objective: Major depressive disorder (MDD) is the leading factor associated with suicidal attempts (SAs) among adolescents, with suicide being the most common cause of mortality in this age group. The present research effort was conducted to explore the predictive utility of support vector machine (SVM)-based analyses of amplitude of low-frequency fluctuation (ALFF) results as a neuroimaging biomarker capable of aiding in the diagnosis of MDD with SA among adolescents. Methods: Resting-state functional magnetic resonance imaging (rs-fMRI) analyses of 71 first-episode, drug-naive adolescent MDD patients with SA and 54 healthy control individuals were conducted. ALFF and SVM methods were used to analyze the resultant imaging data. Results: Relative to healthy control individuals, those adolescent MDD patients with a history of SAs exhibited reductions in ALFF values in the bilateral medial superior frontal gyrus (mSFG) and bilateral precuneus. These lower ALFF values were additionally negatively correlated with Child Depression Inventory (CDI) scores. Moreover, the reduced bilateral precuneus ALFF values were negatively correlated with Suicidal Ideation Questionnaire Junior (SIQ-JR) scores in this patient population. SVM analyses revealed that reductions in the ALFF values of the bilateral mSFG and bilateral precuneus respectively exhibited high diagnostic accuracy levels of 76.8% (96/125) and 82.4% (103/125). Conclusion: The present results demonstrate that adolescent MDD patients with a history of SAs exhibit abnormal ALFF. The abnormal brain regions identified through this research may play a role in the pathogenesis of this condition and may help identify at-risk adolescents. Specifically, reductions in the ALFF in the bilateral mSFG and bilateral precuneus may be indicative of MDD and SA when analyzing adolescent patients.